2020
DOI: 10.1155/2020/9250512
|View full text |Cite|
|
Sign up to set email alerts
|

Dexmedetomidine Postconditioning Alleviates Hypoxia/Reoxygenation Injury in Senescent Myocardial Cells by Regulating lncRNA H19 and m6A Modification

Abstract: H19, a long noncoding RNA (lncRNA), reportedly protects myocardial cells (H9c2 cell line) against hypoxia-reoxygenation- (H/R-) induced injury. Dexmedetomidine (Dex) has an important myocardial protective effect, although its function and mechanism in cardiac ischemia/reperfusion (I/R) injury, especially for senile patients, requires further study. RNA N6-methyladenosine (m6A) is the most abundant endogenous RNA modification. However, the effect of Dex postconditioning on RNA m6A modification has rarely been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…The m6A modified-H19 has been revealed involving in the development of cardiac diseases. In H 2 O 2 -induced senescence, lncRNA H19 expression decreased and m6A modification increased following H/R, ALKBH5 regulated the expression of H19 by mediating its m6A modification levels ( 73 ).…”
Section: M6a Methylation In Cardiac Remodelingmentioning
confidence: 99%
“…The m6A modified-H19 has been revealed involving in the development of cardiac diseases. In H 2 O 2 -induced senescence, lncRNA H19 expression decreased and m6A modification increased following H/R, ALKBH5 regulated the expression of H19 by mediating its m6A modification levels ( 73 ).…”
Section: M6a Methylation In Cardiac Remodelingmentioning
confidence: 99%
“…The combination of METTL3/14 and WATP as a writer, ALKBH5 as an eraser, and YTHDF1 as a reader all influenced the translation of LINC00278 into YY1BM. 130 Zhang et al 131 found that AKLBH5 could regulate the expression of H19, which is a lncRNA, and dexmedetomidine posttreatment could reduce the hypoxia-reoxygenationinduced senile myocardial cell injury by ALKBH5. Highly enriched m 6 A could enhance the RNA stability of LINC00857, and m 6 A-modified LINC00857 upregulation promotes tumorigenesis in pancreatic cancer by regulating the miR-150-5p/E2F3 axis.…”
Section: Role Of M 6 a Methylation In The Regulation Of Tumor-related Lncrnasmentioning
confidence: 99%
“…Additionally, H19 ameliorates ischemia-reperfusion (I/R)-induced myocardial apoptosis or MI-induced myocardial injury by sponging miR-877-3p or miR-22-3p, respectively (91,92). In H9c2 cells with H2O2-induced senescence, H/R enhanced the level of m 6 A methylation and increased the expression of lnc RNA H19 by upregulating ALKBH5 (93). Therefore, the m 6 A modification of H19 is involved in the development of CVD.…”
Section: A Methylation Of Lnc Rnas and Circ Rnas In Cvdsmentioning
confidence: 99%
“…Non-coding RNAs also can regulate m 6 A Micro RNAs such as miR-33a and miR-4429 were found to inhibit METTL3 in the field of tumor studies, indicating that those miRNAs might be as therapeutic agents for CVD (128,129). In addition, lnc RNA H19 has been reported to protect against H2O2induced H9c2 cell apoptosis by up-regulating ALKBH5 (93). Thus, ncRNAs might be used for the regulation of m 6 A and CVD treatment.…”
Section: Modulation Of M 6 a For Cvd Treatmentmentioning
confidence: 99%